Colloidal silica and method for producing the same

A heating-based method for colloidal silica production reduces fine particle content, addressing the issue of surface roughness and yield in semiconductor manufacturing by minimizing residual particles during chemical mechanical polishing.

JP2025015412AActive Publication Date: 2025-01-30FUSO CHEM

Patent Information

Application Number
JP2024062836
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-04-09
Publication Date
2025-01-30
Estimated Expiration
2043-07-19

AI Technical Summary

Technical Problem

Existing colloidal silica used in semiconductor manufacturing processes for chemical mechanical polishing (CMP) contains high levels of fine particles, leading to increased surface roughness and reduced yield due to their residual presence on polishing surfaces.

Method used

A manufacturing method involving heating silica sol at the boiling point of water under normal pressure, combined with specific pH and stirring conditions, to produce colloidal silica with reduced fine particle content.

Benefits of technology

The method significantly reduces the amount of fine particles on the polishing surface, thereby improving surface roughness and yield in CMP processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025015412000001
    Figure 2025015412000001
  • Figure 2025015412000002
    Figure 2025015412000002
  • Figure 2025015412000003
    Figure 2025015412000003
Patent Text Reader

Abstract

To provide colloidal silica with few fine particles.SOLUTION: Provided is a method for producing colloidal silica.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to colloidal silica with a low content of fine particles. [Background technology]

[0002] In the CMP (Chemical Mechanical Polishing) process in semiconductor manufacturing, the residue of particles on the polished surface is often a problem, which leads to a decrease in the yield in semiconductor manufacturing.

[0003] As semiconductors become finer, there is a demand for further reducing the amount of particles remaining on the polished surface, and accordingly, there is a demand for reducing the amount of particles contained in the CMP slurry.

[0004] Colloidal silica is used as an abrasive raw material for CMP slurries. Colloidal silica usually contains a small amount of fine particles smaller than the main particles, which can cause the problem of remaining on the polishing surface.

[0005] Conventionally, methods for producing colloidal silica with few fine particles have been disclosed (Patent Documents 1 and 2). Patent Document 1 discloses that in the hydrolysis and condensation reaction of an alkoxysilane or its condensate, a silica sol with few fine particles is obtained by adjusting the reaction conditions so that the value of the electrical conductivity does not change by 90% or more from 5 minutes after the start of the reaction when the electrical conductivity first reaches a maximum until the end of the reaction. Patent Document 2 discloses that in the hydrolysis and condensation reaction of a tetraalkoxysilane, a silica sol with few fine particles is obtained by limiting the change in water concentration in the reaction system from the start of the hydrolysis and condensation reaction to within 3% by mass.

[0006] In addition, a method of subjecting the produced colloidal silica to a solvent replacement treatment by heating and distilling so that the organic solvent concentration is less than 1 mass% (Patent Document 3), a method of adding a neutral oxidizing agent (Patent Document 4), and a method of reducing fine particles by ultrafiltration using an ultrafiltration membrane (Patent Document 5) have been disclosed. Patent Document 3 discloses that a colloidal silica having a number distribution ratio of fine particles having a particle size of 40% or less of the volume average particle size is obtained by distilling off the organic solvent coexisting with the colloidal silica produced by the sol-gel method so that the residual organic solvent concentration in the colloidal silica produced by the sol-gel method is less than 1 mass%. Patent Document 4 discloses that a silica sol with a small amount of intermediate products (unreacted substances) is obtained by adding a neutral oxidizing agent (including hydrogen peroxide) to a silica sol produced by the sol-gel method. Patent Document 5 discloses that intermediate products are removed by ultrafiltration of a silica sol obtained by subjecting tetraalkoxysilane to hydrolysis and condensation reaction using an ultrafiltration membrane with a molecular weight cutoff of 5,000 to 80,000.

[0007] Even with these conventional techniques, colloidal silica in which the amount of fine particles is reduced to a level sufficient to meet the requirements of semiconductor CMP processes at advanced technology nodes has not yet been obtained. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2020-164351 A [Patent Document 2] JP 2022-109711 A [Patent Document 3] International Publication No. WO2016 / 117560A1 [Patent Document 4] JP 2020-75830 A [Patent Document 5] JP 2021-116208 A Summary of the Invention [Problem to be solved by the invention]

[0009] The present invention provides colloidal silica with few fine particles. [Means for solving the problem]

[0010] As a result of extensive research, the inventors of the present invention have developed a technique for producing colloidal silica with a low content of fine particles by including a specific heat treatment in the colloidal silica production process.

[0011] The present invention encompasses the following colloidal silica and a method for producing the colloidal silica.

[0012] Section 1. A method for producing colloidal silica, comprising the steps of: A process in which silica sol, which consists of water and silica particles, is heated at the boiling point of water under normal pressure. A method for producing colloidal silica, comprising:

[0013] Section 2. The pH of the silica sol during the heat treatment is pH 9.0 to pH 10.5; The heat treatment time is 11 hours to 35 hours. The heat treatment is carried out on silica sol 1m 3 The stirring power per unit is 0.01kW / m 3 ~0.40kW / m 3 The silica sol is stirred under the conditions of Item 1. A method for producing colloidal silica.

[0014] Section 3. The silica sol is (a) Solution B containing an alkoxysilane is added to solution A containing water and an alkali catalyst; (b) A silica sol obtained by hydrolysis and dehydration condensation of alkoxysilane contained in the solution B under the condition that the addition rate of the alkoxysilane contained in the solution B per 1 kg of the solution A is 0.8 mol / hour / kg to 2.50 mol / hour / kg. 3. The method for producing colloidal silica according to item 1 or 2.

[0015] Section 4. The silica sol is (a) Solution B containing an alkoxysilane is added to solution A containing water and an alkali catalyst; (b) A silica sol obtained by hydrolysis and dehydration condensation of an alkoxysilane under conditions in which the concentration of the alkoxysilane contained in the solution B is 60% by mass to 98% by mass. 3. The method for producing colloidal silica according to item 1 or 2.

[0016] Section 5. Colloidal silica, A colloidal silica having a fine particle content parameter 1, defined as follows, of 15.0 or less.

[0017] Definition of fine particle content parameter 1 (i) The colloidal silica is diluted with ultrapure water having an electrical resistivity of 18.2 MΩ or more (hereinafter referred to as "ultrapure water") to a silica concentration of 2 mass % (wt%) (diluted solution).

[0018] (ii) 9.1 g of the diluted solution is transferred to a centrifuge tube (model number: S303922A) manufactured by Eppendorf-Himac Technologies Co., Ltd., and centrifuged using a centrifuge rotor S58A and a centrifuge CS100FNX at a centrifuge speed of 50,000 rpm, a centrifuge temperature of 5°C, and a centrifugation time of 60 minutes (all manufactured by Eppendorf-Himac Technologies Co., Ltd.).

[0019] (iii) After centrifugation, 2 mL of the supernatant is collected from the centrifuge tube, and this 2 mL of the supernatant after centrifugation is mixed with silica sol obtained by diluting ultra-high purity colloidal silica PL-3 manufactured by Fuso Chemical Co., Ltd. 10 times with ultra-pure water in the following mass ratio (mixture).

[0020] After centrifugation, the supernatant: 10-fold dilution of PL-3 = 9:1 (mass ratio) (iv) The particle size distribution of the resulting mixture is measured using a particle size distribution measuring device based on a scanning electrical mobility diameter measurement method.

[0021] (v) The value calculated from the obtained measured particle size distribution value using the following formula (1) is defined as the fine particle content parameter 1 of the colloidal silica.

[0022] Equation (1) Fine particle content parameter 1 = (Total number of particles detected that are 15 nm or less) ÷ (Total number of particles detected that are 25 nm or more) The colloidal silica of the present invention has a small content of fine particles. When the colloidal silica of the present invention is used as an abrasive for CMP, the amount of fine particles remaining on the polished surface is significantly reduced, and the surface roughness of the polished surface can be reduced, compared with the case where conventional colloidal silica is used as an abrasive. Effect of the Invention

[0023] The present invention can provide colloidal silica with few fine particles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] The present invention will be described in detail below.

[0025] The embodiments of the present invention are intended to provide a better understanding of the gist of the invention, and unless otherwise specified, do not limit the content of the invention.

[0026] In this specification, the terms "comprise" and "containing" are concepts which encompass all of "comprise," "consist essentially of," and "consist only of."

[0027] In this specification, when a numerical range is indicated as "A to B," it means "A or more and B or less."

[0028] In this specification, the designations parts, % etc. are generally used.

[0029] In this specification, unless otherwise specified, all parts by mass or % by mass (wt%) are used.

[0030] [1] Method for producing colloidal silica The present invention includes a method for making colloidal silica.

[0031] The method for producing colloidal silica of the present invention includes a step of heat-treating a silica sol consisting of water and silica particles at the boiling point of water under normal pressure.

[0032] The pH of the silica sol during the heat treatment is preferably from pH 9.0 to pH 10.5.

[0033] The heat treatment time is preferably 11 to 35 hours.

[0034] The heat treatment is preferably carried out with 1 ml of silica sol. 3 The stirring power per unit is 0.01kW / m 3 ~0.40kW / m 3 The silica sol is stirred under the conditions described above.

[0035] The silica sol (silica sol consisting of water and silica particles) is preferably (a) Solution B containing an alkoxysilane is added to solution A containing water and an alkali catalyst; (b) A silica sol obtained by hydrolysis and dehydration condensation of alkoxysilane contained in solution B under the condition that the addition rate of alkoxysilane contained in solution B is 0.8 mol / hour / kg to 2.50 mol / hour / kg per 1 kg of solution A.

[0036] The "mol / hour / kg" indicates the mass of alkoxysilane added per hour per kg of solution A, converted into the amount of silica substance.

[0037] The silica sol (silica sol consisting of water and silica particles) is preferably (a) Solution B containing an alkoxysilane is added to solution A containing water and an alkali catalyst; (b) A silica sol obtained by hydrolysis and dehydration condensation of an alkoxysilane under conditions in which the concentration of the alkoxysilane contained in the solution B is 60% by mass to 98% by mass.

[0038] The colloidal silica of the present invention has a small content of fine particles. When the colloidal silica obtained by the production method of the present invention is used as an abrasive for CMP, the amount of fine particles remaining on the polished surface is significantly reduced, and the surface roughness of the polished surface can be reduced.

[0039] The method for producing colloidal silica of the present invention preferably involves a series of operations: (i) synthesizing silica particles by an alkoxide method (particle synthesis), (ii) concentrating the particle concentration by thermal distillation (thermal concentration), (iii) replacing the solvent with water by thermal distillation (heated water replacement), and (iv) reducing the fine particles by heat treatment (heat treatment), which makes it possible to produce colloidal silica with few fine particles.

[0040] (1) Silica particle synthesis process In the method for producing colloidal silica of the present invention, silica particles are preferably obtained by hydrolyzing and dehydrating condensing an alkoxysilane to obtain a silica sol (particle synthesis step by the alkoxide method).

[0041] Three-liquid method (method of synthesizing silica particles) The silica particles are preferably synthesized by a three-liquid method, in which a solution B containing an alkoxysilane (tetraalkoxysilane) and a solution C containing water are added to a solution A containing water, an alkali catalyst, and an alcohol, and the alkoxysilane (tetraalkoxysilane) is subjected to a hydrolysis reaction and a condensation reaction to synthesize the silica particles. The synthesis of the silica particles is preferably performed by a three-liquid method, which provides excellent controllability of the hydrolysis reaction and the condensation reaction.

[0042] Solution A (three-liquid method) In the synthesis of silica particles, a three-liquid method is adopted, and the water concentration (mass %, wt%) of solution A is preferably 3 wt% to 25 wt%, more preferably 3 wt% to 23 wt%, further preferably 3 wt% to 20 wt%, and most preferably 3 wt% to 18 wt%. By adjusting the water concentration of solution A to preferably 3 wt% to 25 wt%, the solubility of silicic acid produced by hydrolysis reaction in the reaction liquid is excellent.

[0043] In the synthesis of silica particles, a three-liquid method is adopted, and the alkali catalyst concentration (mass %, wt%) of solution A is preferably 0.1 wt% to 3.0 wt%, more preferably 0.2 wt% to 2.5 wt%, even more preferably 0.3 wt% to 2.0 wt%, and most preferably 0.5 wt% to 1.6 wt%. By adjusting the alkali catalyst concentration of solution A to preferably 0.1 wt% to 3.0 wt%, aggregation of silica particles is suppressed, and the dispersion stability of the silica particles in the dispersion liquid is excellent.

[0044] The alkali catalyst is preferably an organic base catalyst that does not contain a metal component, in order to avoid contamination with metal impurities, and more preferably an organic base catalyst that contains nitrogen.

[0045] The alkaline catalyst is preferably ammonia.

[0046] The organic base catalyst is preferably ethylenediamine, diethylenetriamine, triethylenetetraamine, urea, monoethanolamine, diethanolamine, triethanolamine, tetramethylammonium hydroxide (TMAH), tetramethylguanidine, 3-ethoxypropylamine (3-EOPA), dipropylamine, triethylamine, or the like.

[0047] Ammonia is preferably used because it has an excellent catalytic action, is highly volatile, and can be easily removed in a subsequent step.

[0048] From the viewpoint of increasing the true specific gravity of the silica particles, it is preferable to select an organic base catalyst having a boiling point of 90°C or higher so that it is unlikely to volatilize even if the reaction temperature is increased. Preferably, tetramethylammonium hydroxide, 3-ethoxypropylamine, etc. are used.

[0049] The alkali catalyst may be used alone or in combination of two or more kinds (blend).

[0050] The alcohol is preferably methanol, ethanol, n-propanol, isopropanol, ethylene glycol, propylene glycol, 1,4-butanediol, or the like.

[0051] The alcohol may be used alone or in combination of two or more kinds (blend).

[0052] Solution B (3 liquid method) The silica sol is preferably (a) Solution B containing an alkoxysilane is added to solution A containing water and an alkali catalyst; (b) A silica sol obtained by hydrolysis and dehydration condensation of an alkoxysilane under conditions in which the concentration (mass %, wt %) of the alkoxysilane contained in the solution B is 60 mass % to 98 mass %.

[0053] In the synthesis of silica particles, a three-liquid method is adopted, and the alkoxysilane concentration of solution B is preferably 60 wt% to 98 wt%, more preferably 65 wt% to 98 wt%, even more preferably 68 wt% to 98 wt%, and most preferably 70 wt% to 95 wt%. By adjusting the alkoxysilane concentration of solution B to preferably 60 wt% to 98 wt%, the amount of solvent used can be reduced, and the productivity of silica particles is excellent.

[0054] The silica sol is preferably (a) Solution B containing an alkoxysilane is added to solution A containing water and an alkali catalyst; (b) A silica sol obtained by hydrolysis and dehydration condensation of alkoxysilane contained in solution B under the condition that the addition rate of alkoxysilane contained in solution B is 0.8 mol / hour / kg to 2.50 mol / hour / kg per 1 kg of solution A.

[0055] In the synthesis of silica particles, a three-liquid method is adopted, and the addition rate (mol / hr / kg) of alkoxysilane in solution B is preferably 0.8 mol / hr / kg to 2.5 mol / hr / kg, more preferably 1.1 mol / hr / kg to 2.4 mol / hr / kg. By adjusting the addition rate of alkoxysilane in solution B to preferably 0.8 mol / hr / kg to 2.5 mol / hr / kg, the reaction time is shortened and productivity is excellent.

[0056] The "mol / hour / kg" indicates the mass of alkoxysilane added per hour per kg of solution A, converted into the amount of silica substance.

[0057] The alkoxysilane is preferably a tetra-C alkoxysilane such as tetramethoxysilane (TMOS), tetraethoxysilane, or tetraisopropoxysilane. 1-8 An alkoxysilane is used. The alkoxysilane is preferably tetra C 1-4 An alkoxysilane is used, and more preferably, tetramethoxysilane (TMOS), tetraethoxysilane, or the like is used.

[0058] The alkoxysilane may be used alone or in combination of two or more kinds (blend).

[0059] The alcohol is preferably methanol, ethanol, n-propanol, isopropanol, ethylene glycol, propylene glycol, 1,4-butanediol, or the like.

[0060] The alcohol may be used alone or in combination of two or more kinds (blend).

[0061] Solution C (3 liquid method) In the synthesis of silica particles, a three-liquid method is adopted, and the alkali catalyst concentration (mass %, wt%) of solution C is preferably 0 wt% to 9 wt%, more preferably 0 wt% to 8 wt%, even more preferably 0 wt% to 7 wt%, and most preferably 0 wt% to 6 wt%. By adjusting the alkali catalyst concentration of solution C to preferably 0 wt% to 9 wt%, the reaction does not proceed excessively slowly, and controllability is excellent.

[0062] The alkaline catalyst is preferably ammonia.

[0063] The organic base catalyst is preferably ethylenediamine, diethylenetriamine, triethylenetetraamine, urea, monoethanolamine, diethanolamine, triethanolamine, tetramethylammonium hydroxide (TMAH), tetramethylguanidine, 3-ethoxypropylamine, dipropylamine, triethylamine, or the like.

[0064] Ammonia is preferably used because it has an excellent catalytic action, is highly volatile, and can be easily removed in a subsequent step.

[0065] From the viewpoint of increasing the true specific gravity of the silica particles, it is preferable to select an organic base catalyst having a boiling point of 90°C or higher so that it is unlikely to volatilize even if the reaction temperature is increased. Preferably, tetramethylammonium hydroxide, 3-ethoxypropylamine, etc. are used.

[0066] The alkali catalyst may be used alone or in combination of two or more kinds (blend).

[0067] Hydrolysis and condensation reactions In the synthesis of silica particles, a three-liquid method is adopted, and the maximum value of the water concentration (mass %, wt%) in the reaction system from the start of the hydrolysis reaction and the condensation reaction to the end of the reaction is preferably 28 wt% or less, more preferably 25 wt% or less, even more preferably 20 wt% or less, and most preferably 18 wt% or less. By adjusting the maximum value of the water concentration in the reaction system from the start of the hydrolysis reaction and the condensation reaction to the end of the reaction, preferably 28 wt% or less, the solubility of alkoxysilane (tetraalkoxysilane, etc.) in the reaction solution is improved, and the generation of fine silica particles can be suppressed.

[0068] In the synthesis of silica particles, a three-liquid method is adopted, and the change in water concentration (mass %, wt%) in the reaction system from the start of the hydrolysis reaction and the condensation reaction to the end of the reaction is preferably 15 wt% or less, more preferably 13 wt% or less, even more preferably 11 wt% or less, and most preferably 8 wt% or less. By adjusting the change in water concentration in the reaction system from the start of the hydrolysis reaction and the condensation reaction to the end of the reaction, preferably 15 wt% or less, the solubility of silicic acid generated by the reaction is maintained, and the generation of fine silica particles can be suppressed.

[0069] In the synthesis of silica particles, a three-liquid method is adopted, and the reaction temperature (°C) is preferably 10°C to 80°C, more preferably 12°C to 70°C, even more preferably 15°C to 60°C, and most preferably 18°C ​​to 55°C. By adjusting the reaction temperature in the synthesis of silica particles to preferably 10°C to 80°C, the reaction does not proceed excessively slowly, and controllability is excellent.

[0070] In the method for producing colloidal silica of the present invention, in addition to a production method in which alkoxysilane is hydrolyzed and subjected to dehydration condensation to obtain a silica sol (a method for synthesizing silica particles by an alkoxide method), a production method in which sodium silicate is ion-exchanged to prepare active silicic acid, and then condensation of silicic acid species under basic conditions to obtain a silica sol may also be used.

[0071] (2)Heating concentration process The method for producing colloidal silica of the present invention preferably includes a heat concentration step, in which the particle concentration is concentrated by heat distillation. By including the heat concentration step in the method for producing colloidal silica, it is possible to reduce the fine particles of silica particles contained in the colloidal silica.

[0072] In the heat concentration step, the Pv value (stirring power per unit volume) is preferably 0.01 kW / m 3 ~0.40kW / m 3 and more preferably 0.01 kW / m 3 ~0.30kW / m 3 and more preferably 0.01 kW / m 3 ~0.20kW / m 3 and most preferably 0.01 kW / m 3 ~0.10kW / m 3 The Pv value of the heat concentration treatment is preferably 0.40 kW / m 3 By adjusting as follows, the concentration and temperature of the silica particles can be made uniform and the Pv value can be kept below a certain value, thereby suppressing the aggregation of the silica particles.

[0073] The heat concentration time (minutes, min) of the heat concentration step is preferably 60 to 600 minutes. By adjusting the heat concentration time of the heat concentration step to preferably 60 to 600 minutes, it is possible to reduce the fine particles of the silica particles without significantly changing the average secondary particle size and the degree of association of the silica particles.

[0074] (3) Heating water replacement process (production of silica sol consisting of water and silica particles) The colloidal silica to be subjected to the heat treatment is preferably one in which the concentration of silica particles has been concentrated by heat distillation and the solvent has been replaced with water. By carrying out heat concentration and replacement with heated water under the following conditions, the content of fine particles of 15 nm or less can be reduced from the point before the heat treatment. By carrying out heat treatment under the above conditions on the colloidal silica with a low fine particle content obtained by heat concentration and replacement with heated water under the following conditions, colloidal silica with an even lower fine particle content can be obtained.

[0075] The method for producing colloidal silica of the present invention preferably includes a heated water replacement step in which the solvent is replaced with water by heated distillation. By including the heated water replacement step in the method for producing colloidal silica, the fine particles of silica particles contained in the colloidal silica can be reduced.

[0076] In the heated water replacement step, the Pv value (stirring power per unit volume) is preferably 0.01 kW / m 3 ~0.40kW / m 3 and more preferably 0.01 kW / m 3 ~0.30kW / m 3 and more preferably 0.01 kW / m 3 ~0.20kW / m 3 and most preferably 0.01 kW / m 3 ~0.10kW / m 3 The Pv value of the heated water replacement treatment is preferably 0.40 kW / m 3 By adjusting as follows, the concentration and temperature of the silica sol can be made uniform and the Pv value can be kept below a certain value, thereby suppressing the aggregation of silica particles.

[0077] The heating water replacement time (minutes, min) in the heating water replacement step is preferably 60 to 600 minutes. By adjusting the heating water replacement time in the heating water replacement step to preferably 60 to 600 minutes, it is possible to reduce the fine particles of the silica particles without significantly changing the average secondary particle size and the degree of association of the silica particles.

[0078] In the heated water replacement step, the methanol concentration (ppm) after the heated water replacement is preferably 10,000 ppm or less, more preferably 5,000 ppm or less, even more preferably 1,000 ppm or less, and most preferably 500 ppm or less. By adjusting the methanol concentration after the heated water replacement to preferably 10,000 ppm or less, it is possible to reduce the fine silica particles contained in the colloidal silica.

[0079] (4) Heat Treatment Step (Method of Producing Colloidal Silica) The colloidal silica to be subjected to the heat treatment is preferably one in which the concentration of silica particles has been concentrated by heat distillation and the solvent has been replaced with water. By heat concentration and replacement with heated water, the fine particle content of silica particles of 15 nm or less can be reduced from the point before the heat treatment. By heat treating the colloidal silica with a low fine particle content of silica particles obtained by heat concentration and replacement with heated water, colloidal silica with an even lower fine particle content can be obtained.

[0080] The method for producing colloidal silica of the present invention includes a step of heat-treating a silica sol consisting of water and silica particles at the boiling point of water under normal pressure. In the method for producing colloidal silica of the present invention, the heat treatment can reduce the fine particles of silica particles contained in the colloidal silica.

[0081] In the heat treatment step, the heating temperature is the boiling point of water and reflux is performed. By heating the mixture at the boiling point of water and refluxing it, it is possible to reduce the fine particles of the silica particles without significantly changing the average secondary particle size and the degree of association of the silica particles.

[0082] In the heat treatment step, the pressure during heating is normal pressure. By performing the heat treatment at normal pressure during heating, it is possible to reduce the fine particles of the silica particles without significantly changing the average secondary particle size and the degree of association of the silica particles.

[0083] The pH of the silica sol during the heat treatment is preferably from pH 9.0 to pH 10.5.

[0084] The pH of the silica sol is preferably adjusted to pH 9.0 to pH 10.5 using 3-ethoxypropylamine (3-EOPA), ammonia, ethylenediamine, diethylenetriamine, or the like.

[0085] The minimum pH value of the silica sol during the heat treatment is preferably 9.0 or more, more preferably 9.2 or more, even more preferably 9.4 or more, and most preferably 9.5 or more. By adjusting the minimum pH value of the silica sol during the heat treatment to preferably 9.0 or more, it is possible to reduce the fine particles of silica particles contained in the colloidal silica.

[0086] The maximum pH value of the silica sol during the heat treatment is preferably 10.5 or less, more preferably 10.3 or less, even more preferably 10.1 or less, and most preferably 10.0 or less. By adjusting the maximum pH value of the silica sol during the heat treatment to preferably 10.5 or less, aggregation of silica particles can be suppressed.

[0087] The heat treatment is preferably carried out with 1 ml of silica sol. 3 The stirring power per unit (Pv value) is 0.01kW / m 3 ~0.40kW / m 3 The silica sol is stirred under the conditions described above.

[0088] In the heat treatment step, the Pv value (stirring power per unit volume) is preferably 0.01 kW / m 3 ~0.40kW / m 3 and more preferably 0.01 kW / m 3 ~0.30kW / m 3 and more preferably 0.01 kW / m 3 ~0.20kW / m 3 and most preferably 0.01 kW / m 3 ~0.10kW / m 3 The Pv value during the heat treatment is preferably 0.40 kW / m 3 By adjusting as follows, the concentration and temperature of the silica sol can be made uniform and the Pv value can be kept below a certain value, thereby suppressing the aggregation of silica particles.

[0089] The heat treatment time is preferably 11 to 35 hours. In the heat treatment step, the heating time (hours) is preferably 11 to 35 hours, more preferably 12 to 30 hours, even more preferably 14 to 28 hours, and most preferably 15 to 25 hours. By adjusting the heat treatment time to preferably 11 to 35 hours, it is possible to reduce the fine particles of the silica particles without significantly changing the average secondary particle size and degree of association of the silica particles.

[0090] In the heat treatment step, the concentration of the silica sol during heating (mass %, wt%) is preferably 2 wt% to 50 wt%, more preferably 4 wt% to 45 wt%, even more preferably 6 wt% to 40 wt%, and most preferably 8 wt% to 35 wt%. By adjusting the concentration of the silica sol during the heat treatment to preferably 2 wt% to 50 wt%, it is possible to reduce the fine particles of the silica particles without significantly changing the average secondary particle size and the degree of association of the silica particles.

[0091] [2] Colloidal silica The present invention includes colloidal silica.

[0092] The colloidal silica of the present invention has a fine particle content parameter 1, defined as follows, of 15.0 or less.

[0093] Definition of fine particle content parameter 1 (i) The colloidal silica is diluted with ultrapure water having an electrical resistivity of 18.2 MΩ or more (hereinafter referred to as "ultrapure water") to a silica concentration of 2 mass % (wt%) (diluted solution).

[0094] (ii) 9.1 g of the diluted solution is transferred to a centrifuge tube (model number: S303922A) manufactured by Eppendorf-Himac Technologies Co., Ltd., and centrifuged using a centrifuge rotor S58A and a centrifuge CS100FNX at a centrifuge speed of 50,000 rpm, a centrifuge temperature of 5°C, and a centrifugation time of 60 minutes (all manufactured by Eppendorf-Himac Technologies Co., Ltd.).

[0095] (iii) After centrifugation, 2 mL of the supernatant is collected from the centrifuge tube, and this 2 mL of the supernatant after centrifugation is mixed with silica sol obtained by diluting ultra-high purity colloidal silica PL-3 manufactured by Fuso Chemical Co., Ltd. 10 times with ultra-pure water in the following mass ratio (mixture).

[0096] After centrifugation, the supernatant: 10-fold dilution of PL-3 = 9:1 (mass ratio)

[0097] (iv) The particle size distribution of the resulting mixture is measured using a particle size distribution measuring device based on a scanning electrical mobility diameter measurement method.

[0098] (v) The value calculated from the obtained measured particle size distribution value using the following formula (1) is defined as the fine particle content parameter 1 of the colloidal silica.

[0099] Equation (1) Fine particle content parameter 1 = (Total number of particles detected that are 15 nm or less) ÷ (Total number of particles detected that are 25 nm or more) The colloidal silica of the present invention has (i) an average secondary particle diameter of 20 nm to 250 nm, and (ii) a fine particle content parameter 1 of 15.0 or less.

[0100] The colloidal silica of the present invention has a small content of fine particles. When the colloidal silica obtained by the production method of the present invention is used as an abrasive for CMP, the amount of fine particles remaining on the polished surface is significantly reduced, and the surface roughness of the polished surface can be reduced.

[0101] The silica concentration (mass %, wt%) of the colloidal silica is preferably 2 wt% to 55 wt%, more preferably 2 wt% to 50 wt%, even more preferably 2 wt% to 45 wt%, and most preferably 3 wt% to 40 wt%. By adjusting the silica concentration of the colloidal silica to preferably 2 wt% to 55 wt%, the polishing rate is excellent.

[0102] [3] Methods for evaluating the physical properties of colloidal silica In the present invention, the physical properties of the silica particles are evaluated as follows.

[0103] (1-1) Method for measuring fine particle content parameter 1 (i) The colloidal silica sample to be measured is diluted with ultrapure water (hereinafter referred to as "ultrapure water") having an electrical resistivity of 18.2 MΩ or more to obtain a silica concentration of 2 mass% (wt%) (diluted solution).

[0104] (ii) 9.1 g of the diluted solution is transferred to a centrifuge tube (model number: S303922A) manufactured by Eppendorf-Himac Technologies Co., Ltd., and centrifuged using a centrifuge rotor S58A and a centrifuge CS100FNX at a centrifuge speed of 50,000 rpm, a centrifuge temperature of 5°C, and a centrifuge time of 60 minutes (all manufactured by Eppendorf-Himac Technologies Co., Ltd.).

[0105] (iii) After centrifugation, 2 mL of the supernatant is collected from the centrifuge tube, and this 2 mL of the supernatant after centrifugation is mixed with silica sol obtained by diluting ultra-high purity colloidal silica PL-3 manufactured by Fuso Chemical Co., Ltd. 10 times with ultra-pure water in the following mass ratio.

[0106] After centrifugation, the supernatant: 10-fold dilution of PL-3 = 9:1 (mass ratio) The resulting mixture was used as measurement sample 1.

[0107] (iv) The particle size distribution of the measurement sample 1 is measured by a particle size distribution measuring device based on a scanning electrical mobility diameter measurement method. An example of a particle size distribution measuring device based on a scanning electrical mobility diameter measurement method is Liquid Nanoparticle Sizer System Model 9310 (LNS) manufactured by KANOMAX, and measurement is performed using the LNS under the following (1-2) particle size distribution measurement conditions.

[0108] (v) From the obtained particle size distribution measurements, calculate the fine particle content parameter 1 of the colloidal silica sample using the following equation:

[0109] Equation (1) Fine particle content parameter 1 = (Total number of particles detected that are 15 nm or less) ÷ (Total number of particles detected that are 25 nm or more)

[0110] (1-2) Particle size distribution measurement conditions (i) The air used for the measurements is compressed air produced by a compressor and then purified and dried using an air filter (CKD, FCS500-88-P90).

[0111] (ii) Supply ultrapure water and the above-mentioned dry air into the LNS device and carry out a pre-operation prior to measurement for at least 24 hours.

[0112] (iii) Use ultrapure water to clean the inside of the measuring device. Measure the particle concentration of the ultrapure water under the conditions shown in Table 1. Cleaning is completed when the total number of detected particles becomes less than 5.0E+11 (# / mL).

[0113] (iv) Under the measurement conditions shown in Table 1, measurement is performed using LNS Volumetric Standard manufactured by KANOMAX Corporation as the standard particles.

[0114] (v) Use ultrapure water to clean the inside of the measurement device. Measure the particle concentration of the ultrapure water under the conditions shown in Table 1. Cleaning is completed when the total number of detected particles becomes less than 1.0E+11 (# / mL).

[0115] (vi) Measurement sample 1 is measured under the measurement conditions shown in Table 1.

[0116] The colloidal silica has a fine particle content parameter 1 of 15.0 or less, measured by the above-mentioned measuring method.

[0117] The colloidal silica has a microparticle content parameter 1 measured by the above-mentioned measuring method of 15.0 or less, preferably 12.0 or less, more preferably 10.0 or less, and even more preferably 8.0 or less. By adjusting the microparticle content parameter 1 to 15.0 or less, the amount of microparticles remaining on the polished surface can be reduced.

[0118] (2-1) Measurement method for fine particle content parameter 2 (%) (i) Add ultrapure water having an electrical resistivity of 18.2 MΩ or more (hereinafter referred to as "ultrapure water") to the colloidal silica sample to be measured, and dilute the sample so that the silica concentration after dilution is 0.1 mass% (wt%). The resulting diluted solution is designated as measurement sample 2.

[0119] (ii) The particle size distribution of the measurement sample 2 is measured by a particle size distribution measuring device based on a scanning electrical mobility diameter measurement method. An example of a particle size distribution measuring device based on a scanning electrical mobility diameter measurement method is Liquid Nanoparticle Sizer System Model 9310 (LNS) manufactured by KANOMAX, and measurement is performed using the LNS under the following (2-2) particle size distribution measurement conditions.

[0120] (iii) From the obtained particle size distribution measurements, calculate the fine particle content parameter 2 of the colloidal silica sample using the following formula:

[0121] Equation (3) Fine particle content parameter 2 = (Total number of particles detected that are 15 nm or less) ÷ (Total number of all particles detected) × 100 [%]

[0122] (2-2) Particle size distribution measurement conditions (i) The air used for the measurements is compressed air produced by a compressor and then purified and dried using an air filter (CKD, FCS500-88-P90).

[0123] (ii) Supply ultrapure water and the above-mentioned dry air into the LNS device and carry out a pre-operation prior to measurement for at least 24 hours.

[0124] (iii) Use ultrapure water to clean the inside of the measuring device. Measure the particle concentration of the ultrapure water under the conditions shown in Table 1. Cleaning is completed when the total number of detected particles becomes less than 5.0E+11 (# / mL).

[0125] (iv) Under the measurement conditions shown in Table 1 (LNS measurement conditions), measurement is performed using LNS Volumetric Standard manufactured by KANOMAX as the standard particle.

[0126] (v) Use ultrapure water to clean the inside of the measurement device. Measure the particle concentration of the ultrapure water under the conditions shown in Table 1. Cleaning is completed when the total number of detected particles becomes less than 1.0E+11 (# / mL).

[0127] (vi) Measurement sample 2 is measured under the measurement conditions shown in Table 1.

[0128] The colloidal silica has a fine particle content parameter 2 of 8.0% or less as measured by the above-mentioned measurement method.

[0129] The colloidal silica has a microparticle content parameter 2 of 8.0% or less, preferably 7.0% or less, more preferably 6.0% or less, and even more preferably 5.0% or less, as measured by the above-mentioned measuring method. By adjusting the microparticle content parameter 2 to 8.0% or less, the amount of microparticles remaining on the polished surface can be reduced.

[0130] [Table 1]

[0131] (3) Percentage of fine particles evaluated by SEM (%) (i) A dispersion liquid containing 7.5 mL of methanol, 1.5 mL of water, 1 mL of 0.01M HCl, and 5 μL of 20% colloidal silica is dropped onto a sample stage and allowed to dry. The sample stage is then set in a scanning electron microscope (SEM) and an SEM image is taken.

[0132] (ii) Images of 1,000 silica particles taken with a scanning electron microscope were each approximated to an ellipse using image analysis software (Mitani Shoji Co., Ltd.'s "WinRoof2018"), and the minor axis of the ellipse was measured.

[0133] (iii) In the number frequency distribution of the minor axis of an ellipse obtained by the above-mentioned SEM image analysis, particles whose minor axis of an ellipse is 25% or less of the average value are defined as fine particles, and the number ratio of fine particles is calculated.

[0134] The proportion of fine particles in the colloidal silica as evaluated by SEM is preferably 0.1% or less. By adjusting the proportion of fine particles in the colloidal silica as evaluated by SEM to 0.1% or less, the amount of fine particles remaining on the polished surface can be reduced.

[0135] (4) Average primary particle diameter (nm) The colloidal silica is pre-dried on a hot plate and then heat-treated at 800°C for 1 hour to prepare a measurement sample. The BET specific surface area is measured using the prepared measurement sample. The true specific gravity of silica is 2.2, and the formula is 2727 / BET specific surface area (m 2 / g) is converted to the average primary particle size (nm) of the silica particles in the colloidal silica.

[0136] The average primary particle size of the colloidal silica is preferably 5 nm to 130 nm, more preferably 10 nm to 120 nm, even more preferably 12 nm to 110 nm, and most preferably 14 nm to 100 nm. By adjusting the average primary particle size of the colloidal silica to preferably 5 nm to 130 nm, the roughness of the polished surface can be reduced.

[0137] (5) Average secondary particle diameter (nm) A 0.3% by mass aqueous solution of citric acid is added to the colloidal silica to dilute it to a silica concentration of 1.0% by mass (wt%) (diluted solution).

[0138] The diluted solution is used as a measurement sample. The measurement sample is used to measure the average secondary particle diameter by dynamic light scattering (ELSZ-2000, manufactured by Otsuka Electronics Co., Ltd.).

[0139] The average secondary particle diameter (nm) of the colloidal silica is preferably 20 nm to 250 nm, more preferably 24 nm to 200 nm, even more preferably 27 nm to 170 nm, and most preferably 30 nm to 140 nm. By adjusting the average secondary particle diameter of the colloidal silica to preferably 20 nm to 250 nm, the roughness of the polished surface can be reduced.

[0140] (6) Association ratio The association ratio of silica particles in colloidal silica is a value obtained by calculating the average secondary particle size / average primary particle size of silica particles in colloidal silica.

[0141] The association ratio of silica particles in the colloidal silica is preferably 1.0 or more, more preferably 1.1 or more, even more preferably 1.2 or more, and most preferably 1.3 or more. By adjusting the lower limit of the association ratio of the colloidal silica to 1.0 or more, the polishing rate when polishing with the colloidal silica is further improved.

[0142] The association ratio of the colloidal silica is preferably 4.0 or less, more preferably 3.5 or less, even more preferably 3.0 or less, and most preferably 2.9 or less. By adjusting the upper limit of the association ratio of the colloidal silica to 4.0 or less, it is possible to reduce the roughness of the polished surface when polishing with the colloidal silica.

[0143] (7) Silica concentration (mass% (wt%)) Colloidal silica was pre-dried on a hot plate, then heat-treated at 800°C for 1 hour, and the residual amount was calculated.

[0144] The silica concentration of the colloidal silica is preferably 2 wt% to 55 wt%, more preferably 2 wt% to 50 wt%, even more preferably 2 wt% to 45 wt%, and most preferably 3 wt% to 40 wt%. By adjusting the silica concentration of the colloidal silica to 2 wt% to 55 wt%, the polishing rate when polishing the colloidal silica is further improved.

[0145] (8) Silanol group density (pcs / nm 2 ) The silanol group density of colloidal silica can be determined by the Sears method. The Sears method was performed with reference to the description in GW Sears, Jr., "Determination of Specific Surface Area of ​​Colloidal Silica by Titration with Sodium Hydroxide", Analytical Chemistry, 28(12), 1981(1956). A 1% by weight (wt%) silica dispersion was used for the measurement, and titration was performed with a 0.1 mol / L aqueous sodium hydroxide solution, and the silanol group density was calculated based on the following formula.

[0146] ρ = (a × f × 6022) ÷ (c × S) In the above formula, ρ: Silanol group density (number / nm 2 ), a: Drop amount (mL) of 0.1 mol / L sodium hydroxide aqueous solution with pH 4-9, f: Factor of 0.1 mol / L sodium hydroxide aqueous solution, c: Mass of silica particles (g), S: BET specific surface area (m 2 / g).

[0147] The silanol group density of the silica particles in the colloidal silica is preferably 1.5 / nm 2 More preferably, it is 1.6 particles / nm 2 More preferably, it is 1.8 particles / nm 2 More preferably, it is 2.0 particles / nm 2 The lower limit of the silanol group density is set to 1.5 / nm 2 By making the above adjustments, the occurrence of scratches on the workpiece is further reduced.

[0148] The silanol group density is preferably 10.0 / nm 2 More preferably, 9.5 particles / nm 2 More preferably, 9.0 particles / nm 2or less, and most preferably 8.8 particles / nm 2 The upper limit of the silanol group density is 10.0 / nm 2 By adjusting the ratio as follows, the polishing ability of the colloidal silica can be further improved.

[0149] (9) True specific gravity In this specification, the true specific gravity can be measured by drying colloidal silica on a hot plate at 150° C., holding it in a furnace at 300° C. for 1 hour, and then subjecting it to a liquid phase substitution method using ethanol.

[0150] The true specific gravity of the silica particles contained in the colloidal silica is preferably 1.0 or more, more preferably 1.2 or more, even more preferably 1.4 or more, and most preferably 1.5 or more. By adjusting the lower limit of the true specific gravity to 1.0 or more, the polishing property of the colloidal silica of the present invention is further improved.

[0151] The true specific gravity is preferably 3.0 or less, more preferably 2.8 or less, even more preferably 2.5 or less, and most preferably 2.3 or less. By adjusting the upper limit of the true specific gravity to 3.0 or less, the occurrence of scratches on the object to be polished is further reduced.

[0152] (10) Metal impurity content (ppm) The content of metal impurities was measured using an atomic absorption spectrometer. The sum of the contents of sodium, potassium, iron, aluminum, calcium, magnesium, titanium, nickel, chromium, copper, zinc, lead, silver, manganese, and cobalt in the colloidal silica was defined as the content of metal impurities.

[0153] The content of metal impurities contained in colloidal silica is preferably 1 ppm or less. By adjusting the content of metal impurities contained in colloidal silica to 1 ppm or less, it is more suitable for use as a CMP slurry.

[0154] (11) Polished surface roughness RMS(nm) The colloidal silica is diluted with ultrapure water to a silica concentration of 3.0 mass % (wt %) to prepare a polishing composition.

[0155] Using the obtained polishing composition, a 3 cm square silicon wafer having a silicon oxide film formed on its surface is polished under the following conditions.

[0156] Polishing machine: NF-300CMP, manufactured by Nanofactor Co., Ltd. Polishing pad: Nitta DuPont Co., Ltd., IC1000TMPad Slurry feed rate: 50 mL / min Head rotation speed: 32 rpm Platen rotation speed: 32 rpm Grinding pressure: 4 psi Polishing time: 2 min After polishing, the surface roughness of the polished surface of the wafer is evaluated using an atomic force microscope under the following conditions.

[0157] Atomic force microscope: Shimadzu Corporation SPM-9700HT Cantilever: OLYMPUS MICRO CANTILEVER OMCL-AC240TS-R3 Observation mode: Dynamic Scanning range: 3.0 μm square Scanning speed: 1.00 Hz Number of observation fields: Five fields are observed per polished wafer.

[0158] Method for calculating surface roughness: The average value of the root mean square roughness of five fields of view was taken as the polished surface roughness RMS.

[0159] The polished surface roughness RMS (nm) is preferably 3.00 nm or less.

[0160] (12) Number of particles remaining on the polished surface (particles / μm 2 ) The colloidal silica is diluted with ultrapure water so that the silica concentration becomes 3.0 mass % (wt %) to prepare a polishing composition.

[0161] Using the obtained polishing composition, a 3 cm square silicon wafer having a silicon oxide film formed on its surface is polished under the following conditions.

[0162] Polishing machine: NF-300CMP, manufactured by Nanofactor Co., Ltd. Polishing pad: Nitta DuPont Co., Ltd., IC1000TMPad Slurry feed rate: 50 mL / min Head rotation speed: 32 rpm Platen rotation speed: 32 rpm Grinding pressure: 4 psi Polishing time: 2 min The polished silicon wafers are cleaned by scrubbing with a PVA roll brush in the scrubbing section built into the cleaning and drying equipment MAT ZAB-8S1M under the following conditions: To hold the silicon wafers in place, a jig made of glass epoxy resin is used for the frame and polyurethane for the wafer fixing part.

[0163] Brush: AION SCL BRUSH ROLLER 48(40 / 26)×224 mm Scrub time: 1 min Brush rotation speed: 200 rpm Spin speed of silicon wafer holder: 50 rpm After scrubbing, ultrapure water is allowed to flow over the polished substrate at 750 mL / min for 1 minute, and the substrate is then treated at 1800 rpm for 20 seconds in a spin dryer installed in the above apparatus.

[0164] After drying, the number of particles remaining on the polished surface of the silicon wafer is counted using an SPM-9700HT manufactured by Shimadzu Corporation.

[0165] Number of particles remaining on the polished surface (particles / μm 2 ) is preferably 3 pieces / μm 2 The following is the result.

[0166] [4] Polishing composition The present invention includes a polishing composition containing the colloidal silica of the present invention.

[0167] The polishing composition is useful for CMP applications.

[0168] The polishing composition contains colloidal silica and may further contain additives such as a diluent, an oxidizing agent, a pH adjuster, an anticorrosive agent, a stabilizer, and a surfactant.

[0169] The content of colloidal silica in the polishing composition (mass%, wt%, silica concentration) is preferably 0.01 wt% to 20 wt%, more preferably 0.1 wt% to 15 wt%, even more preferably 1 wt% to 10 wt%, and particularly preferably 2 wt% to 5 wt%.

[0170] Although the embodiment of the present invention has been described above, the present invention is not limited to these examples. It goes without saying that the present invention can be embodied in various forms without departing from the gist of the present invention. EXAMPLES

[0171] The present invention will now be described in detail with reference to examples.

[0172] However, the present invention is not limited to the examples.

[0173] [1] Production of colloidal silica (1) Example 1 (with heat treatment) Preparation of heated water-displaced silica sol To solution A, which was a mixture of 976 g of methanol, 97 g of water, and 58 g of 29% by mass ammonia water, solution B, which was a mixture of 190 g of methanol and 506 g of tetramethoxysilane (TMOS), and solution C (pH = 7.85) of 119 g of pure water, were added at a constant rate over a period of 75 minutes.

[0174] In preparing the reaction solution, the temperature of each solution before mixing was kept at 35°C, and the temperature of the reaction solution was adjusted so that it decreased from an initial reaction temperature of 35°C at the start of addition of solution B to solution A (start of synthesis) to a final reaction temperature of 24.5°C at the end of addition (end of synthesis), while adding the entire amounts of solutions B and C to solution A at a constant rate.

[0175] The reaction solution was heated and concentrated under stirring, and then the mixture was replaced with heated water. After the replacement with heated water, the methanol concentration was 301 ppm.

[0176] Colloidal silica production (heat treatment) 0.65 parts by mass of 3-ethoxypropylamine (3-EOPA) was added to 100 parts by mass of the silica sol obtained above after the replacement with heated water, the pH was adjusted to 9.9, and the silica sol was heated under stirring and normal pressure at 100° C. The point at which the silica sol reached 100° C. was regarded as the start of the heat treatment, and samples were taken every 0.5 hours from the start of the heat treatment to measure the pH.

[0177] 0.5 hours after the start of the heat treatment, the pH had reached 9.6, so 0.2 parts by mass of 3-EOPA was added again to adjust the pH to 9.9. The above operation was repeated every 1.5 hours from the start of the heat treatment to the end of the heat treatment. 2.2 parts by mass of 3-EOPA was added from the start of the heat treatment to the end of the heat treatment.

[0178] The heat treatment was carried out for 16 hours to obtain colloidal silica.

[0179] Measurement of methanol concentration A gas chromatograph (Thermo, FocusGC), an autosampler (Thermo, AS3000, or a device with equivalent performance or higher), and an air compressor (capable of supplying compressed air of 0.4 MPa or higher) were used. A 1 μL sample was drawn into a 10 μL syringe, and the syringe was set in the autosampler for measurement.

[0180] (2) Example 2 (with heat treatment) Preparation of heated water-displaced silica sol Solution A was prepared by mixing 7.7 g of pure water, 96.8 g of methanol, and 4.5 g of 29% by mass ammonia water. Solution B was prepared by mixing 100 g of TMOS and 17.7 g of methanol, and Solution C was prepared by mixing 31.7 g of pure water and 4.7 g of 29% by mass ammonia water. These were added at a constant rate over a period of 217 minutes while maintaining the liquid temperature at 36°C.

[0181] After the addition was completed, the reaction solution was stirred for an additional 30 minutes while maintaining the temperature of the reaction solution at 36°C.

[0182] The reaction solution was heated and concentrated under stirring, and the mixture was replaced with heated water. After the replacement with heated water, the methanol concentration was 212 ppm.

[0183] Colloidal silica production (heat treatment) 0.6 parts by mass of 3-EOPA was added to 100 parts by mass of the silica sol obtained above after the replacement with heated water, the pH was adjusted to 9.8, and the silica sol was heated under stirring and normal pressure at 100° C. The point at which the silica sol reached 100° C. was regarded as the start of the heat treatment, and samples were taken every 0.5 hours from the start of the heat treatment to measure the pH.

[0184] 0.5 hours after the start of the heat treatment, the pH had reached 9.6, so 0.12 parts by mass of 3-EOPA was added again to adjust the pH to 9.8. The above operation was repeated every 1.0 hour from the start of the heat treatment to the end of the heat treatment. 2.76 parts by mass of 3-EOPA was added from the start of the heat treatment to the end of the heat treatment.

[0185] The heat treatment was carried out for 23.0 hours to obtain colloidal silica.

[0186] (3) Example 3 (heat-treated, small average particle size) Preparation of heated water-displaced silica sol Solution A was prepared by mixing 463.1 g of pure water, 104.8 g of 26% by mass aqueous ammonia, and 4,255.0 g of methanol. Solution B was prepared by mixing 3,044.4 g of TMOS and 229.4 g of methanol, and Solution C was prepared by mixing 643.2 g of pure water and 104.8 g of 26% by mass aqueous ammonia. These were added at a constant rate over a period of 150 minutes while maintaining the liquid temperature at 50°C.

[0187] The reaction solution was heated and concentrated under stirring, and the mixture was replaced with heated water. After the replacement with heated water, the methanol concentration was 198 ppm.

[0188] Colloidal silica production (heat treatment) 0.65 parts by mass of 3-EOPA was added to 100 parts by mass of the silica sol obtained above after the replacement with heated water, the pH was adjusted to 9.9, and the silica sol was heated under stirring and normal pressure at 100° C. The point at which the silica sol reached 100° C. was regarded as the start of the heat treatment, and samples were taken every 0.5 hours from the start of the heat treatment to measure the pH.

[0189] 0.5 hours after the start of the heat treatment, the pH had reached 9.6, so 0.2 parts by mass of 3-EOPA was added again to adjust the pH to 9.9. The above operation was repeated every 1.0 hour from the start of the heat treatment to the end of the heat treatment. 3.2 parts by mass of 3-EOPA was added from the start of the heat treatment to the end of the heat treatment.

[0190] The heat treatment was carried out for 24.5 hours to obtain colloidal silica.

[0191] (4) Example 4 (heat-treated, large average particle size) Preparation of heated water-displaced silica sol Solution A was prepared by mixing 1,546.6 g of pure water, 340.6 g of 26% by mass aqueous ammonia, and 8,363.2 g of methanol. Solution B was prepared by mixing 6,088.0 g of TMOS and 350.0 g of methanol, and Solution C was prepared by mixing 1,186.2 g of pure water and 340.6 g of 26% by mass aqueous ammonia. These were added at a constant rate over a period of 100 minutes while maintaining the liquid temperature at 20°C.

[0192] The reaction solution was heated and concentrated under stirring, and the mixture was replaced with heated water. After the replacement with heated water, the methanol concentration was 196 ppm.

[0193] Colloidal silica production (heat treatment) 0.65 parts by mass of 3-EOPA was added to 100 parts by mass of the silica sol obtained above after the replacement with heated water, the pH was adjusted to 9.9, and the silica sol was heated under stirring and normal pressure at 100° C. The point at which the silica sol reached 100° C. was regarded as the start of the heat treatment, and samples were taken every 0.25 hours from the start of the heat treatment to measure the pH.

[0194] 0.25 hours after the start of the heat treatment, the pH had reached 9.7, so 0.15 parts by mass of 3-EOPA was added again to adjust the pH to 9.9. The above operation was repeated every 1.0 hour from the start of the heat treatment to the end of the heat treatment. 3.0 parts by mass of 3-EOPA was added from the start of the heat treatment to the end of the heat treatment.

[0195] The heat treatment was carried out for 20.0 hours to obtain colloidal silica.

[0196] (5) Example 5 (Example with heat treatment, low silica concentration during heating) Preparation of heated water-displaced silica sol The reaction liquid obtained in Example 1 was subjected to replacement with heated water under stirring conditions. After replacement with heated water, the methanol concentration was 387 ppm.

[0197] Colloidal silica production (heat treatment) 0.65 parts by mass of 3-EOPA was added to 100 parts by mass of the silica sol obtained above after the replacement with heated water, the pH was adjusted to 9.9, and the silica sol was heated under stirring and normal pressure at 100° C. The point at which the silica sol reached 100° C. was regarded as the start of the heat treatment, and samples were taken every 0.5 hours from the start of the heat treatment to measure the pH.

[0198] 0.5 hours after the start of the heat treatment, the pH had reached 9.6, so 0.2 parts by mass of 3-EOPA was added again to adjust the pH to 9.9. The above operation was repeated every 1.5 hours from the start of the heat treatment to the end of the heat treatment. 2.4 parts by mass of 3-EOPA was added from the start of the heat treatment to the end of the heat treatment.

[0199] The heat treatment was carried out for 18.0 hours to obtain colloidal silica.

[0200] (6) Example 6 (Example with heat treatment, high silica concentration during heating) Preparation of heated water-displaced silica sol The reaction liquid obtained in Example 1 was heated and concentrated under stirring conditions, and then replaced with heated water. The methanol concentration after the replacement with heated water was 184 ppm.

[0201] Colloidal silica production (heat treatment) 0.65 parts by mass of 3-EOPA was added to 100 parts by mass of the silica sol obtained above after the replacement with heated water, the pH was adjusted to 9.9, and the silica sol was heated under stirring and normal pressure at 100° C. The point at which the silica sol reached 100° C. was regarded as the start of the heat treatment, and samples were taken every 0.5 hours from the start of the heat treatment to measure the pH.

[0202] After 0.5 hours had passed since the start of heating, the pH had reached 9.6, so 0.2 parts by mass of 3-EOPA was added again to adjust the pH to 9.9. The above operation was repeated every 1.5 hours from the start of the heat treatment to the end of the heat treatment. 2.0 parts by mass of 3-EOPA was added from the start of the heat treatment to the end of the heat treatment.

[0203] The heat treatment was carried out for 15.5 hours to obtain colloidal silica.

[0204] (7) Comparative Example 1 (without heat treatment) This is an example simulating conventional technology (Patent Document 1: JP 2020-164351 A, and Patent Document 3: International Publication No. WO2016 / 117560A1).

[0205] Solution A was prepared by mixing 976 g of methanol, 97 g of water, and 58 g of 29% by mass aqueous ammonia. Solution B was prepared by mixing 190 g of methanol and 506 g of tetramethoxysilane (TMOS), and solution C (pH = 7.85) was prepared by mixing 119 g of pure water, and the solution was added at a constant rate over a period of 75 minutes.

[0206] In preparing the reaction solution, the temperature of each solution before mixing was kept at 35°C, and the temperature of the reaction solution was adjusted so that it decreased from an initial reaction temperature of 35°C at the start of addition of solution B to solution A (start of synthesis) to a final reaction temperature of 24.5°C at the end of addition (end of synthesis), while adding the entire amounts of solutions B and C to solution A at a constant rate.

[0207] The reaction liquid was heated and concentrated under stirring conditions, and then replaced with heated water to obtain colloidal silica.

[0208] (8) Comparative Example 2 (without heat treatment) This is an example simulating the conventional technology (Patent Document 2: JP 2022-109711 A, and Patent Document 3).

[0209] Solution A was prepared by mixing 7.7 g of pure water, 96.8 g of methanol, and 4.5 g of 29% by mass ammonia water. Solution B was prepared by mixing 100 g of tetramethoxysilane and 17.7 g of methanol, and solution C was prepared by mixing 31.7 g of pure water and 4.7 g of 29% by mass ammonia water. These were added at a constant rate over a period of 217 minutes while maintaining the liquid temperature at 36°C.

[0210] After the addition was completed, the reaction solution was stirred for an additional 30 minutes while maintaining the temperature of the reaction solution at 36°C.

[0211] The reaction liquid was heated and concentrated under stirring conditions, and then replaced with heated water to obtain colloidal silica.

[0212] (9) Comparative Example 3 (without heat treatment) This is an example simulating conventional technology (Patent Documents 2-3, and Patent Document 4: JP 2020-75830 A).

[0213] To the colloidal silica obtained in Comparative Example 2, 35% by mass of hydrogen peroxide was added so that the amount of hydrogen peroxide was 0.5 g per 100 g of tetraalkoxysilane converted into silica, thereby obtaining colloidal silica.

[0214] (10) Comparative Example 4 (without heat treatment) This is an example simulating the conventional technology (Patent Documents 2 to 4, and Patent Document 5: JP 2021-116208 A).

[0215] 120 g of the colloidal silica obtained in Comparative Example 3 was ultrafiltered using an ultrafiltration membrane having a molecular weight cutoff of 80,000 (Asahi Kasei Corporation's lab module AOP-0013) in an Asahi Kasei Corporation pencil-type module (PX-02001), Masterflex Corporation's L / S Easy-Load Pump Heads for Precision Tubing, Avantor (MFLX07514-10) and Masterflex Corporation's L / S Analog Modular Drive Replacement Controllers, Avantor (MFLX07559-04) as pumps, and Masterflex Corporation's silicon perhydrolysis tube (96400-25) as tubes, to obtain colloidal silica.

[0216] The amount of liquid that permeated the ultrafiltration membrane was 63.6 g, and the permeability was 53%.

[0217] (11) Comparative Example 5 (Example of long-term ultrafiltration without heat treatment) This is an example simulating the prior art (Patent Documents 2 to 5).

[0218] 40 g of the colloidal silica obtained in Comparative Example 4 was ultrafiltered using an ultrafiltration membrane having a molecular weight cutoff of 80,000 (Asahi Kasei Corporation's lab module AOP-0013) in an Asahi Kasei Corporation pencil module (PX-02001), Masterflex Corporation's L / S Easy-Load Pump Heads for Precision Tubing, Avantor (MFLX07514-10) and Masterflex Corporation's L / S Analog Modular Drive Replacement Controllers, Avantor (MFLX07559-04) as pumps, and Masterflex Corporation's silicon perhydrolysis tube (96400-25) as tubes, to obtain colloidal silica.

[0219] During ultrafiltration, ultrapure water was added to the colloidal silica to maintain the liquid amount of the colloidal silica constant.

[0220] The amount of liquid that permeated the ultrafiltration membrane was 220.5 g, and the time required for ultrafiltration was 152 minutes.

[0221] [Table 2]

[0222] [Table 3]

[0223] [2] Evaluation results Examples 1 to 6 are colloidal silicas produced by a method for producing colloidal silica that includes a step of heat-treating a silica sol consisting of water and silica particles at the boiling point of water under normal pressure.

[0224] The colloidal silica of Examples 1 to 6 had (i) an average secondary particle size of 20 nm to 250 nm, and (ii) a fine particle content parameter 1 of 15.0 or less.

[0225] In the colloidal silica of the examples, the content of fine particles could be reduced.

[0226] Comparative Examples 1 to 5 are colloidal silicas produced by a colloidal silica production method that does not include a heat treatment step.

[0227] Comparative Examples 1 to 5 are examples simulating the prior art.

[0228] Comparative Example 1 is an example simulating Patent Documents 1 and 3, and was unable to effectively reduce fine particles of 15 nm or less.

[0229] Comparative Example 2 is an example simulating Patent Documents 2 and 3, and was unable to effectively reduce fine particles of 15 nm or less.

[0230] Comparative Example 3 is an example simulating Patent Documents 2 to 4, and it was not possible to effectively reduce fine particles of 15 nm or less.

[0231] Comparative Example 4 is an example simulating Patent Documents 2 to 5, and was unable to effectively reduce fine particles of 15 nm or less.

[0232] Comparative Example 5 is an example in which ultrafiltration was carried out for a long period of time in order to simulate Patent Documents 2 to 5 and to reduce the amount of fine particles, and an increase in the average secondary particle size due to particle aggregation was confirmed.

[0233] [3] Industrial Applicability The method for producing colloidal silica of the present invention includes a step of heat-treating a silica sol consisting of water and silica particles at the boiling point of water under normal pressure.

[0234] The colloidal silica of the present invention has (i) an average secondary particle size of 20 nm to 250 nm, and (ii) a fine particle content parameter 1 defined as below of 15.0 or less.

[0235] Definition of fine particle content parameter 1 (i) The colloidal silica is diluted with ultrapure water having an electrical resistivity of 18.2 MΩ or more (hereinafter referred to as "ultrapure water") to a silica concentration of 2 mass % (wt%) (diluted solution).

[0236] (ii) 9.1 g of the diluted solution is transferred to a centrifuge tube (model number: S303922A) manufactured by Eppendorf-Himac Technologies Co., Ltd., and centrifuged using a centrifuge rotor S58A and a centrifuge CS100FNX at a centrifuge speed of 50,000 rpm, a centrifuge temperature of 5°C, and a centrifugation time of 60 minutes (all manufactured by Eppendorf-Himac Technologies Co., Ltd.).

[0237] (iii) After centrifugation, 2 mL of the supernatant is collected from the centrifuge tube, and this 2 mL of the supernatant after centrifugation is mixed with silica sol obtained by diluting ultra-high purity colloidal silica PL-3 manufactured by Fuso Chemical Co., Ltd. 10 times with ultra-pure water in the following mass ratio (mixture).

[0238] After centrifugation, the supernatant: 10-fold dilution of PL-3 = 9:1 (mass ratio) (iv) The particle size distribution of the resulting mixture is measured using a particle size distribution measuring device based on a scanning electrical mobility diameter measurement method.

[0239] (v) The value calculated from the obtained measured particle size distribution value using the following formula (1) is defined as the fine particle content parameter 1 of the colloidal silica.

[0240] Equation (1) Fine particle content parameter 1 = (Total number of particles detected that are 15 nm or less) ÷ (Total number of particles detected that are 25 nm or more) The colloidal silica of the present invention has a low content of fine particles.

[0241] When CMP is performed using the colloidal silica of the present invention as an abrasive, the amount of fine particles remaining on the polished surface is significantly reduced, and the surface roughness of the polished surface can be reduced, compared to when conventional colloidal silica is used as an abrasive.

Claims

1. A method for producing colloidal silica, comprising the steps of: A process in which silica sol, which consists of water and silica particles, is heated at the boiling point of water under normal pressure. A method for producing colloidal silica, comprising:

2. The pH of the silica sol during the heat treatment is pH 9.0 to pH 10.5; The heat treatment time is 11 hours to 35 hours, The heat treatment is carried out on silica sol 1m 3 The stirring power per unit is 0.01kW / m 3 ~0.40kW / m 3 The silica sol is stirred under the conditions of A method for producing the colloidal silica according to claim 1.

3. The silica sol is (a) Solution B containing an alkoxysilane is added to solution A containing water and an alkali catalyst; (b) A silica sol obtained by hydrolysis and dehydration condensation of alkoxysilane contained in said solution B under the condition that the addition rate of alkoxysilane contained in said solution B per 1 kg of said solution A is 0.8 mol / hour / kg to 2.50 mol / hour / kg.

3. A method for producing colloidal silica according to claim 1 or 2.

4. The silica sol is (a) Solution B containing an alkoxysilane is added to solution A containing water and an alkali catalyst; (b) A silica sol obtained by hydrolyzing and dehydrating condensing an alkoxysilane under conditions in which the concentration of the alkoxysilane contained in the solution B is 60% by mass to 98% by mass.

3. A method for producing colloidal silica according to claim 1 or 2.

5. Colloidal silica, A colloidal silica having a fine particle content parameter 1, defined as follows, of 15.0 or less. Definition of fine particle content parameter 1 (i) The colloidal silica is diluted with ultrapure water having an electrical resistivity of 18.2 MΩ or more (hereinafter referred to as "ultrapure water") to a silica concentration of 2 mass % (wt%) (diluted solution). (ii) 9.1 g of the diluted solution is transferred to a centrifuge tube (model number: S303922A) manufactured by Eppendorf-Himac Technologies Co., Ltd., and centrifuged using a centrifuge rotor S58A and a centrifuge CS100FNX under conditions of a centrifuge speed of 50,000 rpm, a centrifuge temperature of 5°C, and a centrifugation time of 60 minutes (all manufactured by Eppendorf-Himac Technologies Co., Ltd.). (iii) After centrifugation, 2 mL of the supernatant is collected from the centrifuge tube, and this 2 mL of the supernatant after centrifugation is mixed with silica sol obtained by diluting ultra-high purity colloidal silica PL-3 manufactured by Fuso Chemical Co., Ltd. 10 times with ultra-pure water in the following mass ratio (mixture). Supernatant after centrifugation: 10-fold dilution of PL-3 = 9:1 (mass ratio) (iv) The particle size distribution of the resulting mixture is measured using a particle size distribution measuring device based on a scanning electrical mobility diameter measurement method. (v) The value calculated from the obtained particle size distribution measurement value using the following formula (1) is defined as the fine particle content parameter 1 of the colloidal silica. Equation (1) Fine particle content parameter 1 = (Total number of particles detected that are 15 nm or less) ÷ (Total number of particles detected that are 25 nm or more)

Citation Information

Patent Citations

  • Silica particle dispersion and its production method

    JP2021054684A

  • Colloidal silica and production method therefor

    WO2023119549A1

  • Method for producing silica sol and method for suppressing intermediate products in silica sol

    JP2020075830A

  • Method for producing silica sol

    JP2020164351A

  • Method for producing silica particle, method for producing silica sol, method for removing intermediate product and polishing method

    JP2021116208A

Cited By

  • Method for producing aqueous-dispersible colloidal silica

    JP2026113418A